If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -4) = 56 Reorder the terms: 2(-4 + 2x) = 56 (-4 * 2 + 2x * 2) = 56 (-8 + 4x) = 56 Solving -8 + 4x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4x = 56 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = 56 + 8 4x = 56 + 8 Combine like terms: 56 + 8 = 64 4x = 64 Divide each side by '4'. x = 16 Simplifying x = 16
| 18-65x=5 | | -3x+(-5)= | | m-12=4 | | x/4=12/7 | | -31=-4b | | 39=3+n | | 4x-14=6+2x | | N^2-5n=-6 | | -2x+(-6)= | | 6x+7=2(3x+7) | | 400/61 | | R^2=-r+6 | | y=4y+9 | | 5y=0-3 | | (x+5)(2x-4)= | | 2x-16=34x | | .9(2x-8)=-1.8 | | -8+2n=-n^2 | | -14+2x=7-x | | 3u-5=2(3-u)-1 | | 17=x+(-35) | | -7.2y=28.8 | | -ax+by=2 | | -3(3x+7)=-9x-21 | | (4999/4999)*x^5=3600/4999 | | -4x-50=58+5x | | -2.59(1-2n)-1.5n= | | (8z^5)(9z^5)= | | 6x-1=6(x+3) | | 2/7(2x-3)=12 | | 5x^2-32x+55=0 | | -5x-7=-3x+11 |